Theoretical Insights into the Solvent Polarity Effect on the Quality of Self-Assembled N-Octadecanethiol Monolayers on Cu (111) Surfaces - Hu, Jun (2018)
The effect of solvent polarity on the quality of self-assembled n-octadecanethiol (C18SH) on Cu surfaces was systematically analyzed using first-principles calculations. The results indicate that the adsorption energy for C18SH on a Cu surface is −3.37 eV, which is higher than the adsorption energies of the solvent molecules. The higher adsorption energy of dissociated C18SH makes the monolayer self-assembly easier on a Cu (111) surface through competitive adsorption. Furthermore, the adsorption energy per unit area for C18SH decreases from −3.24 eV·Å−2 to −3.37 eV·Å−2 in solvents with an increased dielectric constant of 1 to 78.54. Detailed energy analysis reveals that the electrostatic energy gradually increases, while the kinetic energy decreases with increasing dielectric constant. The increased electrostatic energies are mainly attributable to the disappearance of electrostatic interactions on the sulfur end of C18SH. The decreased kinetic energy is mainly due to the generated push force in the polar solvent, which limits the mobility of C18SH. A molecular dynamics simulation also confirms that the -CH3 site has a great interaction with CH3(CH2)4CH3 molecules and a weak interaction with CH3CH2OH molecules. The different types of interactions help to explain why the surface coverage of C18SH on Cu in a high-polarity ethanol solution is significantly larger than that in a low-polarity n-hexane solution at the stabilized stage.